Interpolatory refinement pairs with properties of symmetry and polynomial filling - Gavhi, Mpfareleni Rejoyce (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Mathematics))--University of Stellenbosch, 2008.